Answerable Style : The Idea of the Literary in Medieval England - Grady, Frank; Galloway, Andrew (Book collections on Project MUSE., 2013)
This book addresses medieval literary scholarship and the medieval idea of the literary, with special focus on the poetry of Chaucer, Langland, and Gower.